Recent Advances in Isolation, Synthesis and Biological Evaluation of Terrein. Issue 12 (16th November 2021) - Huang, Dan; Yang, Jianni; Li, Chen; Hui, Yang; Chen, Wenhao
Abstract: Terrein is a small‐molecule polyketide compound with a simple structure mainly isolated from fungi. Since its discovery in 1935, many scholars have conducted a series of research on its structure identification, isolation source, production increase, synthesis and biological activity. Studies have shown that terrein has a variety of biological activities, not only can inhibit melanin production and epidermal hyperplasia, but also has anti‐cancer, anti‐inflammatory, anti‐angiopoietic secretion, antibacterial, insecticidal activities, and so on. It has potential application prospects in beauty, medicine, agriculture and other fields. This article reviews the process of structural identification of terrein since 1935, and summarizes the latest advances in its isolation, source, production increase, synthesis, and biological activity evaluation, with a view to providing a reference and helping for the in‐depth research of terrein. Abstract :